Chapter 9 Lessons in fiscal federalism for Somalia Building fiscal sustainability and national cohesion - Negussie, Solomon (Taylor & Francis, 2023)
Somalia adopted the Provisional Constitution in 2012 and declared itself a federal republic. However, a functioning fiscal arrangement is yet to emerge despite tax reform efforts in Mogadishu and consultations between the federal government and member states. If federalism is to remain Somalia's preference, important choices will have to be made. In reviewing the literature, analysing gaps in the Provisional Constitution, and assessing current practices, this chapter brings to light lessons that could be applied in formalising fiscal federalism in Somalia. These relate, inter alia, to the assignment of functions and revenue sources, the sharing of natural resource revenue, and the strengthening of financial and administrative structures at all levels. The chapter also highlights the need to broaden the federal government's taxation and spending powers beyond the Benadir region, to create a common economic space, and to ensure access to public goods for all.